Pemodelan dan Konsepsi Belajar Siswa pada Materi Gerak Parabola di Berbagai Jenjang Pendidikan: Kajian Meta-Analisis - Wahyuni, Sri; Nadia, Anisa Zulfa (Lontar Physics Today, 2024)
This article examines the relationship between education level, learning media or model, and students' learning conception through a meta-analysis approach. The research focuses on how learning needs at each level of education influence the selection of effective learning media and models to support students' understanding. The combination of technology-based modeling, such as interactive simulations, with constructivistic learning models, such as problem-based learning (PBL), proved effective in increasing interest in learning while correcting misconceptions. This approach identifies that understanding students' initial conceptions is critical to building adaptive and meaningful learning. The results of the analysis show that the level of education plays a significant role in determining the optimal teaching strategy, with different needs in primary, secondary and tertiary students. This article contributes to the development of more targeted and relevant learning methods according to the needs of students at various levels of education.Â